Management decision-making process at General Viejo Technical High School - Palacios Palacios, Ana Gabriela (2013)
The purpose of this research is essential to analyze the management decision making process at General Viejo Technical High School, located in Perez Zeledon, San Jose Province, Costa Rica. This is a descriptive study with qualitative technical support for analyzing the information with the purpose of understanding the data in terms of the educational reality to which it responds. .Among the findings, it is evident that in the management process that is conducted the educational community does not participate, because decisions are taken by the professional in education administration and respected by the faculty and administration, primarily. This generates dissatisfaction among personnel that is open to listen to and participate actively in this process.